Association between somatic cell count during the first lactation and the cumulative milk yield of cows in Irish dairy herds - Archer, Simon C.; Mc Coy, Finola; Wapenaar, Wendela; Green, Martin J. (American Dairy Science Association, 2014)
Reduced potential milk yield is an important component of mastitis costs in dairy cows. The first aim of this study was to assess associations between somatic cell count (SCC) during the first lactation, and cumulative milk yield over the first lactation and subsequent lifetime of cows in Irish dairy herds. The second aim was to assess the association between SCC at 5 to 30 d in milk during parity 1 (SCC1), and SCC over the entire first lactation for cows in Irish dairy herds. The data set studied included records from 51,483 cows in 5,900 herds. Somatic cell count throughout the first lactation was summarized using the geometric mean and variance of SCC. Data were analyzed using linear models that included random effects to account for the lack of independence between observations, and herdlevel variation in coefficients. Models were developed in a Bayesian framework and parameters were estimated from 10,000 Markov chain Monte Carlo simulations. The final models were a good fit to the data. A 1-unit increase in mean natural logarithm SCC over the first lactation was associated with a median decrease in first lactation and lifetime milk yield of 135 and 1,663 kg, respectively. A 1-unit increase in the variance of natural logarithm SCC over the first lactation was associated with a median decrease in lifetime milk yield of 719 kg. To demonstrate the context of lifetime milk yield results, microsimulation was used to model the trajectory of individual cows and evaluate the expected outcomes for particular changes in herd-level geometric mean SCC over the first lactation. A 75% certainty of savings of at least €199/heifer in the herd was detected if herd-level geometric mean SCC over the first lactation was reduced from ≥120,000 to ≤72,000 cells/mL. The association between SCC1 and SCC over the remainder of the first lactation was highly herd dependent, indicating that control measures for heifer mastitis should be preferentially targeted on an individual-herd basis toward either the pre- and peripartum period, or the lactating period, to optimize the lifetime milk yield of dairy cows.